INFLUENCE OF SINTERING TEMPERATURES ON MULTIFERROIC PROPERTIES OF LEAD-FREE BNT-BT-NZF MULTIFERROIC COMPOSITE FABRICATED VIA THE SOLID-STATE COMBUSTION TECHNIQUE - Chongsatan, Wistsarut; Boonpluk, Wiranchana; Vittayakorn, Naratip; Pinitsoontorn, Supree; Jantaratana, Pongsakorn; Rittidech, Aurawan; Bongkarn, Theerachai (My University, 2025)
There has been a growing interest in multiferroics, materials that combine magnetic and electric ordering, over the past few years. This research investigates the influence of sintering temperature (1075-1175°C for 2 hours) on multiferroic properties of 0.7(0.94Bi0.5Na0.5TiO3-0.06BaTiO3)-0.3(Ni0.7Zn0.3Fe2O4) (BNT-BT-NZF) multiferroic composites, fabricated using solid-state combustion with glycine as a fuel was investigated. The XRD patterns of all ceramics revealed the coexistence of a rhombohedral ferroelectric phase, a tetragonal ferroelectric phase, and a cubic ferromagnetic phase. The average grain size, dielectric constant (εr), dielectric loss (tanδ), remnant polarization (Pr), and coercive field (Ec) tended to increase from 0.66 to 2.5μm, 314 to 829, 0.22 to 0.51, 0.36 to 5.82 μC/cm2, and 7.05 to 26.96 kV/cm, respectively, with increase of sintering temperature. The composite ceramics exhibited peak saturation magnetization (Ms ~ 12.21 emu/g) and magnetoelectric (ME) coupling (~ 3.59 mV/cmOe) when sintered at 1150°C.
Keywords: BNT-BT-NZF; Ferromagnetic; Magnetoelectric; Solid-state combustion